A Rapid Assessment: Insect Diversity Around the Stingless Bee Colony in Edufarm Universitas Andalas - Ilmi, Miftahul; Henny Herwina; Dahelmi; Alponsin; Jasmi; Rusdimansyah (Universitas Andalas, 2025)
Insects dominate the animal kingdom, comprising nearly 80% of all animal species, with around 250,000 species found in Indonesia. Among these, stingless bees are a diverse group with over 60 genera. Some stingless bees are cultivated in meliponiculture, practiced around homes and plantations. This study aimed to assess insect diversity near stingless bee colonies in the Education Farm (Edufarm), Universitas Andalas, through a rapid assessment conducted over two days in May 2024. A transect was established with three U-shaped sub-transects surrounding a stingless bee colony. The modify quadra protocol sampling (honey bait traps, leaf litter, soil cores, and hand collecting) was used around the colony. The study identified 1153 individuals from 6 orders, 9 families, and 15 species of insects, with Formicidae from Hymenoptera being the most dominant. This research offers valuable insights into insect diversity around stingless bee colonies at Edufarm and can inform better management strategies for stingless bees and the ecological structure of surrounding environments.